Regarding “Enhancing Predictive Accuracy for Acute Herpetic Neuralgia Treatment: A Fresh Perspective on Pulsed Radiofrequency Therapy Research” [Response to Letter] - Zhao C; Lu Z; Hua B; Yue J; Yang Q; Ni H; Yao M (Journal of Pain Research)
Chengcheng Zhao,1,2 Ziwei Lu,1,2 Bohan Hua,1,2 Jiayu Yue,2 Qinru Yang,2 Huadong Ni,2 Ming Yao2 1Jiaxing University Master’s Degree Cultivation Base, Zhejiang Chinese Medical University, Jiaxing City, Zhejiang, People’s Republic of China; 2Department of Anesthesiology and Pain Research Center, the Affiliated Hospital of Jiaxing University, Jiaxing City, Zhejiang, People’s Republic of ChinaCorrespondence: Ming Yao, Email jxyaoming@zjxu.edu.cn